Mississippi’s 2011 Concealed Carry Law:: Analyzing Reported Criminality among Mississippi’s Public Community Colleges - Doss, Daniel Adrian; McElreath, David Hughes; Gokaraju, Balakrishna; Mallory, Stephen L.; Tesiero, Raymond; Taylor, Linda; Hong, Qiuqi; Jones, Don; McElreath, Leisa Stuart; Parker, McKenzie (Journal of Interdisciplinary Studies in Education, 2020)
This study examined differences in reported campus criminality on selected community college campuses in the years between 2005 and 2016 representing the years preceding and succeeding the implementation of Mississippi’s 2011 concealed carry legislation. Each campus included in this study was a public-funded community college in Mississippi. Using a significance level of 0.05 and an analysis of variance approach, the hypothesis testing showed five statistically significant findings reflecting the cases of Copiah-Lincoln, East Central, Jones County, Mississippi Delta, and Northeast Mississippi Community Colleges. Regarding these outcomes, an analysis of the means showed overall lowered crime reports.